DEKOMPOSISI TERMAL PROPELAN KOMPOSIT BERBASIS AMONIUM PERKLORAT/HYDROXY TERMINATED POLYBUTADIENE (AP/HTPB) (THE THERMAL DECOMPOSITION ANALYSIS OF AMMONIUM PERCHLORATE/HYDROXYTERMINATED POLYBUTADIENE (AP/HTPB) COMPOSITE SOLID PROPELLANT) - Dewi, Wiwiek Utami; Ismah, Yulia Azatil (Indonesian Journal of Aerospace, 2016)
Thermal decomposition process of AP/HTPB solid propellant type RUM, 450 and 1220 were investigated by DTG60 (Differential Thermogravimetric) with operational parameters: temperature 30 – 400oC, nitrogen flow rate 50 ml/min, and heating rate 2.5 C/min. Thermal decomposition analysis will be the first step of decomposition kinetics research in determining life time of the propellant. TGA curve of propellant RUM was found to be two staged meanwhile the thermal decomposition of propellant 450 and 1220 has become one staged. The DTA curve/thermogram of propellant RUM show the formation of intermediate product before full-length decomposition. Unlike propellant RUM, DTA curves of propellant 450 and 1220 do not show the formation of intermediate product. Decomposition process of propellant 450 and 1220 accelerate by Al presence. The difference between AP modal on propellant 450 and 1220 show insignificance effect to the amount of decomposition energy consumption.